2018
DOI: 10.1007/s11306-018-1339-7
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite secretion in microorganisms: the theory of metabolic overflow put to the test

Abstract: Introduction Microbial cells secrete many metabolites during growth, including important intermediates of the central carbon metabolism. This has not been taken into account by researchers when modeling microbial metabolism for metabolic engineering and systems biology studies. Materials and MethodsThe uptake of metabolites by microorganisms is well studied, but our knowledge of how and why they secrete different intracellular compounds is poor. The secretion of metabolites by microbial cells has traditionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 122 publications
0
60
0
Order By: Relevance
“…GEMs do not explicitly consider regulation, whose effects are better reflected in the global transcriptome and the metabolome. [10][11][12][13][14] FBA approaches have been extended with RNAseq and metabolomics data to capture cell regulation and more accurately describe cellular metabolic behavior. 15 For example, transcriptional regulation of gene expression has been linked to GEMs, either by taking into account the absolute expression values, scoring genes and subsequently reaction fluxes as active or non-active based on their expression, [16][17][18] or by incorporating relative gene-expression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GEMs do not explicitly consider regulation, whose effects are better reflected in the global transcriptome and the metabolome. [10][11][12][13][14] FBA approaches have been extended with RNAseq and metabolomics data to capture cell regulation and more accurately describe cellular metabolic behavior. 15 For example, transcriptional regulation of gene expression has been linked to GEMs, either by taking into account the absolute expression values, scoring genes and subsequently reaction fluxes as active or non-active based on their expression, [16][17][18] or by incorporating relative gene-expression.…”
Section: Introductionmentioning
confidence: 99%
“…15 For example, transcriptional regulation of gene expression has been linked to GEMs, either by taking into account the absolute expression values, scoring genes and subsequently reaction fluxes as active or non-active based on their expression, [16][17][18] or by incorporating relative gene-expression. 14,18 Use of relative gene expression is assuming that the relative changes between two conditions correlate with the resulting differential flux profiles. Both approaches can lead to conditionspecific GEMs that are more effective for inferring the actual biochemical activity and the observed physiology of the microorganism.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed greatest inhibition obtained by B. circulans against K. pneumoniae biofilm with percentage of 93.6% and the lowest inhibition recorded by B. cereus against P. aeruginosa biofilm with percentage of 21.7%. This may be due to presence of some extracellular and intracellular metabolites in the medium where intracellular can release into extracellular medium when accumulated in the cell and this has been explained by the metabolic overflow theory [47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…) due to imbalanced intracellular metabolic pathways (Pinu et al . ). In response to environmental conditions, metabolite secretion can be seen as a fundamental biochemical function which reflects the internal metabolic state of microbial cells.…”
Section: Intracellular Metabolites Extracellular Metabolites and Thementioning
confidence: 97%
“…Yet, it has been observed that metabolites which do not accumulate within the cell are directly excreted into the extracellular medium in response to environmental signals (Pinu et al . ).…”
Section: Intracellular Metabolites Extracellular Metabolites and Thementioning
confidence: 97%